2014
DOI: 10.1007/s00464-014-3663-y
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic pretransplant nephrectomy with morcellation in autosomic-dominant polycystic kidney disease patients with end-stage renal disease

Abstract: In our preliminary series and in the hands of a very experienced laparoscopist, LNM for ADPKD appears as a modern, mini-invasive, and safe technique. Specimen's extraction through a small abdominal incision reduces postoperative pain and incisional hernias and guarantees the final cosmetic result of laparoscopy. The reduced overall morbidity could reduce the period between nephrectomy and transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…All 16 studies were retrospective analyses of an exclusively ADPKD cohort, and utilised histological examination of native nephrectomy specimens to assess for the presence of RCC [6, 10, 11, 16‒28]. Studies were published between 1987 and 2022 and examined nephrectomy specimens from 1,147 ADPKD patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All 16 studies were retrospective analyses of an exclusively ADPKD cohort, and utilised histological examination of native nephrectomy specimens to assess for the presence of RCC [6, 10, 11, 16‒28]. Studies were published between 1987 and 2022 and examined nephrectomy specimens from 1,147 ADPKD patients.…”
Section: Resultsmentioning
confidence: 99%
“…As such, 82 RCCs were detected in total. Thirteen papers stated the total number of kidneys analysed, reporting 73 RCCs amongst 1,493 kidneys [6, 10, 11, 16, 17, 21‒28]. Following meta-analysis, the per-kidney prevalence was 4.3% (95% CI, 3.1–5.7, I 2 = 15.7%) (shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We do not consider it a good option to section the kidney or open the cysts while in the peritoneal cavity, due to their often infected content, which can potentially cause prolonged postoperative ileus or peritonitis-like syndrome. 27 Although the incidence of neoplasms on polycystic kidneys is the same as that in the general population, 28 we do not consider it correct to perform the morcellation of the surgical specimen as suggested by some authors 29 due to the risk, albeit low, of neoplastic dissemination and However, in the case of massive polycystic kidneys, the need for a large final incision to extract the intact specimen compromises the aesthetic result. In these cases it is preferable, in our opinion, to proceed immediately with such an incision and use a hand-port for the hand-assisted procedure (HALN).…”
Section: Discussionmentioning
confidence: 97%
“…The laparoscopic morcellator is a device that is not familiar to urologists; however, the application of this equipment has recently been reported in some urologic diseases. Asimakopoulos et al [20] reported on tissue retrieval performed using a laparoscopic morcellator in a case series of huge laparoscopic autosomal-dominant polycystic nephrectomies. However, this study was the first attempt to report tissue removal with a laparoscopic morcellator using a PNV.…”
Section: Discussionmentioning
confidence: 99%